Encryption System based on a Structured Matrix: Vandermonde Matrix - Hana Ali-Pacha; Naima Hadj-Said; Adda Ali-Pacha (IAES Indonesia Section, 2017)
The development of communications and digital transmissions have pushed data encryption to grow quicklyto protect the information against any hacking or digital plagiarisms. Also, the matrix computation algorithmsdeveloped since the fifties exploit different types of structures more algebraically. In this work, we willpropose an encryption system based on the Vandermonde matrix, to secure the data in the form of images.Some orders will be advanced MatLab programming.